Max Min Ant System and Capacitated p-Medians: Extensions and Improved Solutions - O. de França, F.; J. Von Zuben, F.; N. de Castro, L. (Informatica)
Max Min Ant System and Capacitated p-Medians: Extensions and Improved Solutions